2008
DOI: 10.1177/109158180802704s01
|View full text |Cite
|
Sign up to set email alerts
|

Final Amended Report on the Safety Assessment of Methylparaben, Ethylparaben, Propylparaben, Isopropylparaben, Butylparaben, Isobutylparaben, and Benzylparaben as used in Cosmetic Products

Abstract: Coal Tar is a semisolid by-product obtained in the destructive distillation of bituminous coal, which functions in cosmetic products as a cosmetic biocide and denaturant--antidandruff agent is also listed as a function, but this is considered an over-the-counter (OTC) drug use. Coal Tar is a nearly black, viscous liquid, heavier than water, with a naphthalene-like odor and a sharp burning taste, produced in cooking ovens as a by-product in the manufacture of coke. Crude Coal Tar is composed of 48% hydrocarbons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(21 citation statements)
references
References 206 publications
(181 reference statements)
1
20
0
Order By: Relevance
“…2015). Parabens are used as preservatives in cosmetics, personal care products, food, and some pharmaceuticals (Andersen 2008). Benzophenone-3 is an ultraviolet light filter used in sunscreen, clear plastic packaging, and other products to prevent damage to color and scent (e.g., soap, perfumes) (IARC 2013).…”
Section: Introductionmentioning
confidence: 99%
“…2015). Parabens are used as preservatives in cosmetics, personal care products, food, and some pharmaceuticals (Andersen 2008). Benzophenone-3 is an ultraviolet light filter used in sunscreen, clear plastic packaging, and other products to prevent damage to color and scent (e.g., soap, perfumes) (IARC 2013).…”
Section: Introductionmentioning
confidence: 99%
“…This is supported by the lack of sensitization in signal transducer and activator of transcription 6 (STAT6)-deficient mice, which have a defect in Th2 differentiation. 17) However, diisopropyl adipate (DIPA; an alternative plasticizer) was found to induce only marginal IL-4 but abundant IFN-γ production by draining lymph nodes in BALB/c mice. 12) In the present study, DBP was confirmed to augment both IL-4 and IFN-γ production (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The non-antibiotic components of NPD ointment have been shown to cause allergic hypersensitivity reactions, but as previously discussed, the concentrations required for this are 100 to 1000-fold greater to what is found in the NPD compound studied [4, 6]. Similarly, dexamethasone has been associated with a very low rate of allergic contact skin reactions [5].…”
Section: Discussionmentioning
confidence: 99%
“…Each of the agents in this combined steroid/anti-infective ophthalmic ointment has been individually investigated for the incidence of topical allergic contact dermatitis—a type IV hypersensitivity reaction [4, 5]. Polymyxin B has a low sensitization rate, and there is not sufficient evidence to discourage its use because subsequent topical exposure to the antigen is unlikely to cause an allergic contact dermatitis [68].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation